Isolation of yeast genes with mRNA levels controlled by phosphate concentration. - Kramer, R A (1980)
A library of DNA from the yeast, Saccharomyces cerevisiae, was constructed in phage lambda Charon 4 vector and then screened by differential plaque filter hybridization for genes induced by phosphate starvation. Two EcoRI fragments of 7.9 and 5.0 kilobase pairs that contained such genes were isolated. These cloned fragments may each carry one of the several copies of the genes for the repressible acid phosphatase of yeast. The fragments were use to examine mRNA levels of these genes in regulatory mutants of acid phosphatase.